An investigation exploring whether poor menstrual health management causes school learners’ absenteeism, in Ward 4 of the Senqu District Municipality, of the Eastern Cape province of South Africa - Naidoo, Dhee (University of Pretoria, 2024)
Thesis (PhD (Development Studies))--University of Pretoria, 2024.